Genome-wide identification of the soybean cytokinin oxidase/dehydrogenase gene family and its diverse roles in response to multiple abiotic stress - Du, Yanli; Zhang, Zhaoning; Gu, Yanhua; Li, Weijia; Wang, Weiyu; Yuan, Xiankai; Zhang, Yuxian; Yuan, Ming; Du, Jidao; Zhao, Qiang (Frontiers in Plant Science, 2023)
Cytokinin oxidase/dehydrogenase (CKX) irreversibly degrades cytokinin, regulates growth and development, and helps plants to respond to environmental stress. Although the CKX gene has been well characterized in various plants, its role in soybean remains elusive. Therefore, in this study, the evolutionary relationship, chromosomal location, gene structure, motifs, cis-regulatory elements, collinearity, and gene expression patterns of GmCKXs were analyzed using RNA-seq, quantitative real-time PCR (qRT-PCR) and bioinformatics. We identified 18 GmCKX genes from the soybean genome and grouped them into five clades, each comprising members with similar gene structures and motifs. Cis-acting elements involved in hormones, resistance, and physiological metabolism were detected in the promoter regions of GmCKXs. Synteny analysis indicated that segmental duplication events contributed to the expansion of the soybean CKX family.The expression profiling of the GmCKXs genes using qRT-PCR showed tissue-specific expression patterns. The RNA-seq analysis also indicated that GmCKXs play an important role in response to salt and drought stresses at the seedling stage. The responses of the genes to salt, drought, synthetic cytokinin 6-benzyl aminopurine (6-BA), and the auxin indole-3-acetic acid (IAA) at the germination stage were further evaluated by qRT-PCR. Specifically, the GmCKX14 gene was down-regulated in the roots and the radicles at the germination stage. The hormones 6-BA and IAA repressed the expression levels of GmCKX1, GmCKX6, and GmCKX9 genes but up-regulated the expression levels of GmCKX10 and GmCKX18 genes. The three abiotic stresses also decreased the zeatin content in soybean radicle but enhanced the activity of the CKX enzymes. Conversely, the 6-BA and IAA treatments enhanced the CKX enzymes activity but reduced the zeatin content in the radicles. This study, therefore, provides a reference for the functional analysis of GmCKXs in soybean in response to abiotic stresses.